2002
DOI: 10.1073/pnas.022057199
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen availability alters the expression of carnivory in the northern pitcher plant, Sarracenia purpurea

Abstract: Atmospheric transport and deposition of nutrients, especially nitrogen, is a global environmental problem with well-documented consequences for ecosystem dynamics. However, monitoring nitrogen deposition is relatively expensive, monitoring stations are widely spaced, and estimates and predicted impacts of nitrogen deposition are currently derived from spatial modeling and interpolation of limited data. Ombrotrophic (''rain-fed'') bogs are nutrient-poor ecosystems that are especially sensitive to increasing nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
115
5
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(129 citation statements)
references
References 34 publications
7
115
5
2
Order By: Relevance
“…bogs. Ellison and Gotelli (2002) showed that by elevating soil nitrogen levels, pitchers of S. purpurea were reduced relative to phyllodia size resulting in an increase in the rate of Mean values (±SD, n = 6) of light-saturated area-based photosynthesis (P Nmax (area) ), light-saturated mass-based photosynthesis (P Nmax(mass) ), dark respiration (R D ), light compensation point (PPFD comp ), convexity factor (k), and apparent photosynthetic quantum yield (α, P N /PPFD at low PPFD). Means followed by different letters indicate significant differences in P Nmax (area) and R D between greenhouse-and field-collected Drosera rotundifolia (Student's t-test, p< 0.05).…”
Section: Discussionmentioning
confidence: 97%
“…bogs. Ellison and Gotelli (2002) showed that by elevating soil nitrogen levels, pitchers of S. purpurea were reduced relative to phyllodia size resulting in an increase in the rate of Mean values (±SD, n = 6) of light-saturated area-based photosynthesis (P Nmax (area) ), light-saturated mass-based photosynthesis (P Nmax(mass) ), dark respiration (R D ), light compensation point (PPFD comp ), convexity factor (k), and apparent photosynthetic quantum yield (α, P N /PPFD at low PPFD). Means followed by different letters indicate significant differences in P Nmax (area) and R D between greenhouse-and field-collected Drosera rotundifolia (Student's t-test, p< 0.05).…”
Section: Discussionmentioning
confidence: 97%
“…There is no evidence as yet that D. rotundifolia actually attracts prey (Foot et al 2014); but investment in prey capture (through the production of sticky mucilage) is reduced when root N availability is increased experimentally (Thorén et al 2003), which might be the mechanism here. Such a reduction in investment in prey capture has not been demonstrated in-situ for D. rotundifolia but has been shown for Sarracenia purpurea by Ellison and Gotelli (2002). Changes in other parts of the process should, however, not be discounted; the production of digestive enzymes, for example, also carries a metabolic cost and so the plants might reduce enzyme production, thus reducing rates or efficiency of prey digestion.…”
Section: Discussionmentioning
confidence: 99%
“…Some carnivorous plants, such as pitcher plants (Ellison & Gotelli 2002), bladderworts (Englund & Harms 2003) and different species of sundew (Thorén et al 2003), have been found to reduce their investment in carnivory (e.g. produce fewer traps) in response to increased nutrient levels.…”
Section: Discussionmentioning
confidence: 99%